Постановка задач анализа региональных особенностей социально-экономического развития Республики Карелии как северного приграничного субъекта Российской Федерации - Kovshov A. S. (Economics and management: problems, trends and future development, 2017)
at the level of subjects of the Russian Federation economic problems require specific approaches to improve the motivation of economic entities and specific efforts to consolidate its activities for development of the region.
Keywords: инвестиционная деятельность; Республика Карелия; investment; Republic of Karelia; рыночное понимание; market understanding